Tourism Structure Plan of Busuanga and Coron, Northern Palawan: Comprehensive Development through Tourism - Tomeldan, Michael V. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment, 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} Comprehensive Development Planning is undertaken at different scales (i.e. national, regional, provincial, and city or municipal levels) that consider several issues in different sectors. Comprehensive Development Plans or Multi-sector plans, therefore, consists of several sector plans (i.e. economic plans, social development   plans, economic plans, institutional plans, infrastructure plans, environmental management plans, and land use plans) that are interrelated and harmonized. In an effort to decentralize governance and to transform Local Governments Units into self-reliant communities, the Local Government Code of 1991 (Republic Act No. 7160) was enacted by the Congress of the Philippines. The Local Government Code devolved many of the powers, authority, responsibilities and resources to the Local Government Units (i.e. cities and municipalities). Among the responsibilities transferred to the LGU is the formulation of a “Comprehensive Development Plan” that has come in the form of the Comprehensive Land Use Plan (CLUP). The land use plan, as the physical translation of the LGU’s vision, goals and all sector plans, is considered the centerpiece of the Comprehensive Land Use Plan. In the CLUPs of most cities and municipalities, tourism is considered an economic activity and therefore merely incorporated as a sub-sector in the economic plan. Tourism, however, is recognized as a major economic activity that contributes significantly to GNP and creates tremendous employment and livelihood opportunities. Many sub-regions and LGUs have tourism as their main economic activity and many more have resources and potentials for major tourism development. Such LGUs or areas should pay more attention to planning their tourism development. Tourism Planning is a specialized field that is also comprehensive in its approach looking into structure planning, environmental management, land use planning, tourism marketing, tourism product development, human resource development, community planning, etc. Tourism Planning should be undertaken correctly to support comprehensive and sustainable development.